GAMBARAN KADAR ASAM URAT PADA WANITA MENOPAUSE DI PANTI SOSIAL TRESNA WERDHA ILOMATA KECAMATAN SIPATANA KOTA GORONTALO TAHUN 2019 - Anggraini Djibran; Dede Sutriono; Gayatri D. Soga (Journal of Health, Technology and Science (JHTS), 2020)
Uric Acid is the final product of purine metabolism. Uric acid in the hu-man body is produced by the body (endogenous uric acid) and comes from food (exogenous uric acid). About 80-85% of uric acid is produced by the body, while the rest comes from food, which can trigger uric acid in women who are postmenopause due to a decrease in the hormone estrogen which can not produce normal estrogen hormones and also because of factors from a lot of food contain purines. The purpose of this study was to determine levels of uric acid in menopause women, distribution of uric acid levels, a history of gout in menopause women. This research is a descriptive quantitative research approach. The ins-pection method used is spectrophotometry. The sampling technique in total sampling with a total sample of 26 respondents group of elderly menopause women. The results of a study conducted on 26 respondents based on the distri-bution of uric acid levels obtained as many as 21 with a percentage (80.8%) of respondents who are not normal and as many as 5 respondents with a percentage (19.2%) declared normal, whereas based on the distribution of diet there are 5 respondents in the percentage (19.2%) were low purine and 21 respondents with a percentage (80.8%) high purine. Conclusion as many as 21 respondents who experienced abnormal uric acid because respondents consume foods that are high in purines.